Designing and Evaluating a high-reliable and security-aware Identity and Access Management for Slicing Architectures - Moreira, Rodrigo; Carvalho, Tereza C. M. B.; Silva, Flávio de Oliveira (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF); 2023: Anais do XIV Workshop de Pesquisa Experimental da Internet do FuturoDO - 10.5753/wpeif.2023.722, 2023)
Network slicing architectures are fundamental for providing connectivity to demanding users and applications in heterogeneous network infrastructures. Such architectures have evolved significantly in recent years, especially with improvements in security and reliability functions. However, the improvements in these architectures are functionally specific and are not considered throughout the entire architecture lifecycle, opening opportunities for secure, and reliable native architectures. Thus, this paper designs and evaluates an Identity and Access Management (IAM) mechanism while providing security and reliability for building blocks of slicing architectures. Our findings concern a comparative evaluation of the IAM mechanism and its behavior under stress loads, as well as an experimental assessment of a secure defense mechanism against Distributed Denial-of-Service (DDoS) attacks.